Effect of Theta Burst Stimulation-Patterned rTMS on Motor and Nonmotor Dysfunction of Parkinson's Disease: A Systematic Review and Metaanalysis - Cheng, Bo; Zhu, Tao; Zhao, Wenhao; Sun, Ling; Shen, Yao; Xiao, Wei; Zhang, Shushan (Frontiers in Neurology, 2022)
Background: Theta burst stimulation (TBS), a variation of rTMS, affords a short stimulation duration, low stimulation pulse intensity, and a possibility to improve the efficiency of traditional rTMS. Since the therapeutic effect of TBS on the symptoms of patients with PD was inconsistent among different studies. We systematically search these studies and quantitatively analyze the therapeutic effect of TBS for these patients. Methods: We followed the recommended PRISMA guidelines for systematic reviews and meta-analysis. Studies from PubMed, EMBASE, CENTRAL, and ClinicalTrials.gov from the inception of each database to 1 May 2021. We also manually retrieved studies of reference. Results: Seven eligible studies with 167 participants (received real TBS and/or sham TBS) were included. TBS significantly improved the motor section of the Unified Parkinson’s Disease Rating Scale (UPDRS‐III) score for patients with PD compared to sham TBS in the “on” anti-Parkinsonism medicine (APM) state (SMD = -0.31; 95% CI, -0.56 to -0.05; P=0.02; I2=16%), while, there was no significant benefits in the “off” APM state (SMD = -0.13; 95% CI, -0.54 to 0.27; P=0.52; I2=0%).Whether in the condition of “on” APM or “off” APM, TBS had insignificant therapeutic effect on upper limb motor symptom (SMD = -0.08; 95% CI, -0.37 to 0.21; P= 0.60; I2=0%, and SMD =-0.10; 95% CI, -0.46 to 0.26; P=0.59; I2=0%, respectively). Similarly, TBS had no significant effectiveness on gait disorder in the “on” APM state (SMD = -0.05; 95% CI, -0.29 to 0.19; P=0.69; I2=0%). In addition, TBS had a short-term (within 2 weeks) antidepressant effect on PD depression in the “on” APM state (MD =- 2.93; 95% CI, -5.52 to -0.33; P=0.03; I2=8%). Conclusion: TBS can significantly improve the total motor disorder (by improvement of UPDRS-III score) for patients with PD in the "on" APM state. While it has no significant therapeutic effect on the dysfunction of upper limb movement and gait when evaluating the efficacy, separately. In addition, TBS has a short-term (within two weeks) antidepressant effect on PD depression.